PERAN SISTEM KONTROL MANAJEMEN DALAM PENCAPAIAN KINERJA STRATEGIK - Syafruddin, Muchamad (JURNAL BISNIS STRATEGI, 2004)
The objective of this research is to obtain and formulate fitness and properness between the differences strategic patterns tor the companies characterized differences and the management control systems also characterized difference. Based on the analytical study, this research shows that there are differences strategic patterns tor the companies characterized differences. The differences strategic patterns include of entrepreneurial, adaptive, and planning mode (Mintzberg, 1973a); performance-maximizing, sales-maximizing, and cost-minimizing (Utterback and Abernathy 1975); defender, prospector, analyzer, and reactor (Miles and Snow 1978); andoverall cost leadership, differentiation, and focus (Porter 1980). This research also shows that optimum performance can be achieved by congruence between the differences strategic patterns tor the companies characterized differences and the management control systems also characterized difference.